Water splitting with screw pitched cylindrical electrode and Fe(OH)2 catalyst under 1.4 V. (March 2021) - Das, Jagat; Sahu, Partha Pratim
Abstract: Electrochemical water splitting has brought clean route of green energy generation through its hydrogen evolution capability having no environment impact in the form of global warming. The related technology experiences challenges associated with cost, durability and mass production of hydrogen separated from water. Proper morphological design of highly active and low cost materials for both electrodes and electro-catalyst has become essential to deal with these issues. Here iron alloy cylindrical electrodes with screw pitched morphology and low cost ferrous hydroxide nano-particles have been introduced as an electrode and electro-catalyst respectively in compact integrated water electrolysis cell to catalyze both reactions in same electrolyte. Theoretical model of screw pitched electrode has been made to enhance sharp surface area for efficient Hydrogen and Oxygen evolution. It demonstrates water electrolysis using low cell voltage of 1.68 V at current density of 500 mA/cm 2 with long term durability over 80 h having utilization efficiency of 73.88% and Faradaic efficiency of 80.714%. The experiments including high speed synthesis of nano-catalysts performed at room temperature provide guarantee of saving energy. This works promises a significant move towards mass production of hydrogen fuel through inexpensive method of water splitting. Highlights: Compact water splitting setup with screw cylindrical Fe alloy electrode is reported. Due to use of nano-electro-catalyst Fe(OH)2, water splitting occurs at 1.35 voltage. Utilization efficiency of 73.88% and faradaic efficiency of 80.71% are obtained. Experiment with synthesis occurred at room temperature provide saving of energy.